Teste do degrau incremental em pacientes com hipertensão pulmonar: análise de concordância com o cicloergômetro - Vieira, Elaine Brito [UNIFESP] (2019)
Introduction: Cardiopulmonary exercise testing (CPET) on a treadmill or cycle ergometer provides integrated assessment of the cardiorespiratory system during exertion and is widely used in clinical practice. An incremental step test (iStepT) can be an alternative for eliciting maximal exercise responses. Objectives: We sought to analyse the agreement of metabolic, cardiovascular, ventilatory and gas exchange between the incremental step test (iStepT) and incremental protocol performed in the cycloergometer (iCYCLE) in patients with pulmonary hypertension (PH). Methods: 20 patients with precapillary PH (65% female, 41±15 yrs) randomly performed a symptom-limited CPET on cycle ergometer (iCYCLE). Metabolic, cardiovascular, ventilatory and gas exchange variables were recorded during both tests. Bland Altman diagrams were used to verify the concordance between variables from iStepT and iCYCLE. Variable that was not stemming from gas analyser, as number of climbed steps, was analysed through corrrelation of it and known severity assessment markers in pulmonary hypertension. The linear regression analysis was used to establish an equation to predict VO2 from IST variables. Results: There was a greater dessaturation and V̇ O2PEAK in iStepT than cycloergometer. The V̇O2GET , FC PEAK (% pred), ΔV̇ E/ΔV̇ CO2 and ΔHR/Δ V̇ O2 were similar on iStepT and iCYCLE. By linear regression analyses, work of the IST [W = (mass x 9,8 m/s2 x vertical distance)] was a predictor of peak VO2 independent of the sex and age (r2= 0,77, p=0,001). Equation: Peak VO2 pred (mL) = 440,29 + (0,032 x work). Conclusions: iStepT elicited maximal cardiopulmonary responses and has a good agreement with known severity assessment markers in patients with pre capillary PH and the iStepT shown to have more abillity to detect dessaturation effort induced than iCYCLE.